TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA (ADD) DALAM PEMBANGUNAN DESA (Studi Kasus desa Pecatu Kec. Kuta Selatan Kab. Badung Tahun 2017) - Oktavia, Claudya; Noak, Piers Andreas; Winaya, I Ketut (CITIZEN CHARTER, 2019)
ABSTRACT This study aims to determine the extent to which the application of the principles of Transparency and Accountability to manage village fund allocation (ADD) in Pecatu Village, South Kuta Regency, Badung Regency in 2017 in developing villages and based on Village Law No. 6 of 2014 and Permendagri No. 113 of 2014. This study uses a qualitative descriptive methodology. The results of this study indicate that the allocation of village funds in this village has applied the principle of accountability supported by the principle of transparency in stages. the preparation of the RPJM was prepared with the community through village meetings. In realizing transparency in managing the Village Fund Allocation, Pecatu Village provides information to the community through village meetings and the installation of billboards in front of the village office. Therefore, in Pecatu village it is transparent and accountable, but there are still weaknesses which are obstacles that must be overcome. Keywords: Village Fund Allocation (ADD), Transparency and Accountability